MODERN APPROACHES TO DETERMINE THE PERMEABILITY OF RESERVOIR ROCKS BASED ON THE RESULTS OF GEOPHYSICAL INVESTIGATIONS - Shynkarenko, А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Permeability of rock is its physical property that describes its ability to conduct fluids under the pressure gradient. This paper presents short description and analysis of methods for determination of permeability of oil and gas reservoirs. Permeability is a function of different parameters that leads to difficulties during its estimation. Investigations of the void space structure of rocks, their anisotropy etc.were carried out in order to take into account all factors that have an influence on the permeability. Reservoir conditions could also be modeled for that purpose. Methods for determination of permeability of rocks can be divided into three groups: methods based on the laboratory studies of rocks; methods based on the well logging data; and methods based on the correlations between different parameters of rocks. The first two groups include methods for steady and unsteady fluid flow. Methods for the unsteady flow are usually more precise and rapid, thus prospects of extension of methods for permeability determination are mostly connected with them. Each of the presented methods to determine permeability is characterized by some pros and cons. The most appropriate method for the specific experiment is always chosen according to conditions and requirements and expected results. Further author's investigations will be related to the creation of petrophysical models of permeability of oil and gas reservoir rocks, including reservoirs of complex structure.
Keywords: permeability; reservoir rock; petrophysics; well logging; void space structure; porosity